EDUCAÇÃO MORAL NA ESCOLA: CAMINHOS PARA A CONSTRUÇÃO DA CIDADANIA - Rita Melissa Lepre (Colloquium Humanarum, 2005)
The main purpose of this article is to reflect on moral education at school and its role in the construction of the citizen-student, in the search for the building of his autonomy. For such intent we present the conception of moral education proposed by some Spanish authors who continue and improve Piaget's ideas. Thereafter we propose an analysis of the school as a place for moral education focusing its possibilities and limitations.